A STUDY ON THE MAIN CHARACTER’S INTERNAL AND EXTERNAL CONFLICTS IN EXTREMELY LOUD AND INCREDIBLY CLOSE MOVIE - SARI, DWI YUNITA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Freud’s three harmonious personality systems is an important need to be reached by human in their lives. The three systems must be organized well, so that people can satisfy their needs and wants. If the three systems do not work well, it will produce conflicts, include internal and external conflict. In fact, people will feel worry, anxious, and angry in their life in facing and passing their conflicts. This condition is reflected in a movie entitled Extremely Loud and Incredibly Close. The movie tells about the journey of a-nine-years-old-boy named Oskar in facing the conflicts in his life. Therefore, the author will answer the problems formulation of this study: (1) how the main character’s internal conflicts happen in the story (2) how the main character’s external conflicts happen in the story.  This study uses a psychological approach to analyze and interpret data. This study uses a qualitative approach to describe the events clearly and systematically.  The result of this study shows that Oskar, the main character of the movie Extremely Loud and Incredibly Close, reaches his satisfaction because he successfully gets his wants after he faces conflicts in his life. For the next researchers, it is recommended for students majoring on literature to analyze the character’s conflicts from psychoanalysis point of view. Keywords: main character, internal and external conflicts, Freud’s three systems of personality.